THE ROLE AND MAIN TASKS OF LINGUOCULTURAL SCIENCE IN CONTEMPORARY LINGUISTICS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article is dedicated to the methods of linguocultural analysis of the text, the emergence of linguoculturology, stages of development and text analysis.